IMPACT OF RME-BASED E-MODULES ON ENHANCING STUDENTS' UNDERSTANDING OF FUNCTIONS AND CRITICAL THINKING - Pramartha, I Nyoman Bagus; Suharta, I Gusti Putu; Sudiarta, I Gusti Putu; Astawa, Wayan Puja (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study is based on the fact that mathematics learning materials have been unappealing, causing students to quickly become bored and saturated with the learning situation. This has resulted in students not actively participating in lectures, revealing a low level of student conceptual understanding and critical thinking in the context of functions. The research focuses on developing an interactive e-module specifically for university students on the topics of properties and operations of functions, function composition, inverse functions, and function limits, particularly for those in the Information Systems program at ITB Stikom Bali. The e-module, which integrated RME principles such as contextual problems and self-directed learning, was tested using a development research design based on the Plomp model with three methodological phases: preliminary research, development or prototyping phase, and assessment phase. The research data collection methods udes were from questionnaires for lecturer and students, observation results of lecturer and students during the trial, interviews with lecturers and students, also essay tests for students. The results of the Paired Sample T-Test, it is known that the p-value = 0.000 < 0.05, indicating a significant difference between the pre-test and post-test scores in students’ conceptual understanding and critical thinking abilities. Additionally, an RME-based e-module was developed with the following characteristics: (1) provides instructions that facilitate self-directed learning for contextual problems, supported by GeoGebra technology; (2) Incorporates RME characteristics (both “model of” and “model for”) to enhance critical thingking and conceptual understanding; (3) Not dependent on other teaching materials because its content is interconnected and self-sufficient; (4) interctive and adapts to technological advancements, making it accessible on both Android and iOS devices; and (5) Allows for independent evaluation through quiz questions and formative tes questions using Google Forms features. The study offers a model for future applications of RME in higher education.Penelitian ini didasari pada bahan belajar matematika selama ini tidak menarik, sehingga membuat mahasiswa cepat jenuh dan bosan dalam situasi belajarnya. Hal tersebut mengakibatkan mahasiswa tidak berperan aktif dalam perkuliahan, yang mengungkap rendahnya tingkat pemahaman konseptual dan berpikir kritis mahasiswa dalam konteks fungsi. Penelitian ini berfokus pada pengembangan e-modul interaktif yang dirancang khusus untuk mahasiswa pada topik sifat dan operasi fungsi, komposisi fungsi, invers fungsi dan limit fungsi, khususnya pada program studi Sistem Informasi di ITB Stikom Bali. E-modul yang mengintegrasikan prinsip-prinsip RME, seperti masalah kontekstual dan pembelajaran mandiri, diuji dengan desain penelitian pengembangan berdasarkan model Plomp dengan 3 tahapan metode, yaitu preliminary research, development/ fase prototyping, dan assessment. Metode pengambilan data penelitian yang digunakan berasal dari hasil kuesioner untuk dosen dan mahasiswa, hasil observasi terhadap dosen dan mahasiswa selama uji coba, wawancara kepada dosen dan mahasiswa, serta tes esay yang ditujukan untuk mahasiswa. Hasil uji Paired Sample T-Test, diketahui nilai p = 0.000 < 0.05, sehingga ada perbedaan yang signifikan antara skor pre-test dan post-test dalam pemahaman konsep dan kemampuan berpikir kritis mahasiswa. Selain itu, telah dihasilkan e-modul berbasis RME dengan karakteristik: (1) terdapat instruksi yang membantu belajar secara mandiri terhadap masalah kontekstual difasilitasi teknologi GeoGebra; (2) memiliki karakteristik RME (model of dan model for) untuk kemampuan berpikir kritis dan pemahaman konsep; (3) tidak tergantung pada bahan ajar lain karena memiliki sajian materi saling terkoneksi; (4) interaktif dengan mengadaptasi perkembangan IPTEK yang dapat diakses dari android dan iOS; dan (5) dapat melakukan evaluasi secara mandiri pada soal kuis dan soal tes formatif menggunakan fitur Googleform. Penelitian ini menawarkan model untuk aplikasi RME di pendidikan tinggi di masa depan.